Phasing out of the Universal Mega Dose of Vitamin-A Prophylaxis to Avoid Toxicity - Sudip Bhattacharya; Amarjeet Singh (AIMS Press, 2017)
Childhood blindness due to corneal ulceration was prevalent among poor Indian children. To tackle this situation, the National Institute of Nutrition (NIN), Hyderabad, India, Vitamin-A (Vit-A) prophylaxis programme was launched nationally in 1970 after field testing. Research of Indian Council for Medical Research (ICMR) documented that prevalence of Vit-A deficiency signs such as Bitot's spot decreased among children, over a period of time. However, this decrease cannot be ascertained is due to mass Vit-A prophylaxis programme. This is because coverage was low and patchy. Improved nutrition status, wider vaccination coverage, increased rate in breast feeding and improvement of healthcare services played a crucial role. Rather many studies revealed that (mass prophylaxis to the child who is having adequate Vit-A level) it may be harmful to certain group of children as a result of acute toxic symptoms. High dose of Vit-A is capable of loss of bone density-hence retarded growth may be observed in susceptible individuals. To tackle this issue food based approach should be promoted (which includes breast feeding) along with timely measles vaccination. The children who have signs of Vit-A deficiency (e.g. night blindness, xeropthalmia, Bitot's spot) or post measles children should receive Vit-A in age specific daily doses for two weeks along with Vit-A rich food, like green leafy vegetables, red palm oil, liver etc. Public spirited citizens, together with scientific community in India, should discourage this "one size fit to all" approach. It will not only avoid the ill effects of high dose of Vit-A but also it will help us optimal utilization of health resources in a resource poor country like India.